Optimizing radiology in the new picture archiving and communication system environment - Cook, Jay F. (Springer-Verlag, 1997)
Picture archiving and communications systems (PACS) have inescapably altered the face of radiology. Images are available to radiologists and clinicians alike, nearly instantaneously. For patient care management, service has improved, but without inclusion of input from radiologists. Effecting timely report availability requires reorganization of radiology. In a hospital-wide PACS environment, we undertook to render a preliminary report on all nonprocedural computed radiography examinations within 30 minutes in a teaching environment. Two periods of time in the same month were analyzed, one before reorganization and one after. Of 686 reports, 117 were examined with a statistical significance of α=.05 (95% confidence) and a power of 90%. Average times for examination acquisition to preliminary report availability on the PACS decreased from 5 hours to 31 minutes. Standard deviation in report generation times decreased from 8 hours to 30 minutes. This preliminary study suggests that business process reengineering can effect improvement in information flow within a teaching facility resulting in radiologists rejoining the patient care management team. Successes, pitfalls, and future requirements are discussed.